Strategy for Successful Use of E-learning at the Islamic University of Nusantara Bandung - Aisyah, Ia Siti; Nugraha, Mulyawan Safwandy (Journal of Education and Teaching Learning, 2024)
The use of e-learning in higher education has become a basic need, especially since the drastic changes in learning methods due to the pandemic. Islamic University of Nusantara Bandung faces challenges in optimizing the implementation of e-learning to maintain the quality of learning. This study aims to analyze the strategy for the success of implementing e-learning by considering aspects of digital infrastructure readiness, lecturer competence, and student adaptability. Using a qualitative-descriptive approach, the study was conducted through in-depth interviews with 25 lecturers and 150 students, direct observation of the online learning process, and documentation analysis for two academic semesters. The results of the study indicate that the success of e-learning at Islamic University of Nusantara Bandung is supported by three main pillars: continuous training for lecturers in the use of digital learning technology, development of interactive learning content tailored to student characteristics, and responsive technical support. Another interesting finding was the significant increase in student participation through online discussion forums which reached 85%, compared to conventional methods which were only 60%. This study also revealed that the integration of Islamic values ??in e-learning content has a positive impact on student learning motivation. These strategies have proven effective in increasing learning satisfaction by up to 78% based on student feedback surveys.